Low-Voltage Diagnosis of Energy Distribution Network Based on Improved Particle Swarm Optimization Algorithm - Wang, Ting; Ma, Bingfeng; Dai, Xiaohui; Li, Jianfeng; Li, Sheng (Wireless communications and mobile computing, 2022)
In order to improve the research on low-voltage fault diagnosis of energy distribution network, a low-voltage multiobjective diagnosis of AC/DC energy distribution network based on ICHPSO is proposed in this paper. Firstly, the types of objective functions are listed, the objective function is transformed into a single-objective function by using the linear weighting method, and the hybrid particle swarm optimization (HPSO) diagnosis algorithm is improved, which can guide the particles to escape from the local optimal solution space, prevent the particles from falling into the local optimal too early, and improve the search accuracy and global search ability of the algorithm. At the same time, the individuals with high fitness are retained, and the convergence performance of the algorithm is improved. Then, the algorithm is coded, and an example of AC/DC energy distribution network with improved ieee33 is adopted. DC side data comes from the first 13 nodes of AC side data, and the voltage level is 10 kV. The diagnostic effects of different schemes were compared. The results show that the expected mean value of node voltage deviation after power compensation diagnosis is 2.26%, which is 61.18% lower than that before diagnosis; the expected average voltage loss is 0.77 kv, which is 52.1% lower than that before diagnosis; the expectation of network loss is 196.45 kw, which is 49.56% lower than that before diagnosis; the minimum voltage of the AC side node (node 18) is expected to be 0.9514 p.u., 2.75% higher than that before diagnosis; and the minimum voltage of DC side node (node 8) is expected to be 0.9918 p.u., 1.11% higher than that before diagnosis. The comprehensive experimental results show that the proposed method can greatly reduce the node voltage deviation, voltage loss, and network loss of AC/DC energy distribution network, improve the node voltage quality, and maintain the stable operation of the whole AC/DC energy distribution network.